Comparison of visual and haptic feedback during training of lower extremities - Koritnik, T.; Koenig, A.; Bajd, T.; Riener, R.; Munih, M. (Gait & posture, 2010)
We compared the effects of visual and haptic modalities on the adaptation capabilities of healthy subjects to the virtual environment. The visual cueing (only the reference motion is presented) and visual feedback (the reference motion as well as the current tracking deviation are presented) were provided by a real-time visualization of a virtual teacher and a virtual self – avatar, using optical measurements. The subjects had to track the virtual teacher during stepping-in-place movements. The haptic feedback was provided by the actuated gait orthosis Lokomat programmed with the same stepping movements employing an impedance control algorithm. Both setups included auditory cueing. The stepping task was performed by engaging different modalities separately as well as combined. The results showed that (1) visual feedback alone yielded better tracking of the virtual teacher than visual cueing alone, (2) haptic feedback alone yielded better tracking than any visual modality alone, (3) haptic feedback and visual feedback combined yielded better tracking than haptic feedback alone, and (4) haptic feedback combined with visual cueing did not improve tracking performance compared to haptic feedback alone. In general, we observed a better task performance with the haptic modality compared to visual modality.